Synthesis, Characterization and Rheological Studies of Novel Acrylic Acid-co-Acrylonitrile-co-N-Isopropylacrylamide Terpolymeric Hydrogels - Aslam Malana, Muhammad; Parveen, Sidra; Beenish Qureshi, Raheela; Saleem Khan, Muhammad (Asian Journal of Chemistry, 2015)
The primary objective of this research work is the extensive rheological characterization of novel N-isopro-pylacrylamide (NIPAAM) based hydrogels. N-isopropylacrylamide being a temperature sensitive component can alter flow behaviour and drug release characteristics of topical gels in the form of change in their viscosities with temperature and variation in the network structure with their composition. Terpolymeric hydrogels of acrylic acid-co-acrylonitrile-co-N-isopropylacrylamide (AA-AN-NIPAAM) with different concentrations of N-isopropylacrylamide were synthesized by free radical polymerization method. Oscillatory and transient shear measurements were carried out to study viscoelastic properties, effect of temperature on flow behaviour and yield strength of novel pharmaceutical gel formulations. Results indicate a remarkable temperature dependency of the N-isopropylacrylamide based physically cross linked hydrogels. Flow curves plotted at a range of temperature point out a reasonable pseudoplastic behaviour, the most facilitating property of topogels. The hydrogels have acquired a suitable yield strength requisite to rupture their polymeric network structure. The trends of dynamic moduli (G' and G") and relaxation time with N-isopropylacrylamide contents indicate presence of necessary mechanical strength required for the settlement of the gels and controlled release of the drug. Conclusively the rheological behaviour of these novel gels is found to be favourable for applying as controlled and sustained targeted drug delivery.